Understanding and Learning to Do Teacher Education in an Introductory Methods Course. Issue 1 (2nd January 2022) - Chey, Won Seok; Trainer, Scott W.; Ward, Phillip
ABSTRACT: The development of a teacher educator requires a sustained, systematic, and critical inquiry into one's own practice. The purpose of this study was to explore how two doctoral students, in their first semester of doctoral study, understood how to do physical education teacher education in an introductory teaching method class, through the lens of socialization theory. This was a collaborative self-study using an interpretative phenomenological analysis. Three themes were identified. First, social justice and its sub-themes: (a) challenges in changing habited behaviors, (b) social justice issues embedded in the class material, and (c) understanding diversity, change, and the importance of adaptability. Second, practice-based teacher education and its two sub-themes: (a) alignment between theory and practice, and (b) core teaching practices. Third, adapting to the COVID-19 environment and sub-themes of: (a) environmental constraints, (b) improving while being online, and (c) creating a supportive and caring atmosphere in the breakout sessions. Our recommendations include using self-study as a tool to help doctoral students understand and do teacher education.